2010
DOI: 10.1097/sla.0b013e3181c1cfc9
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Mobility, ASA Status and Administration of Tramadol are Risk Factors for Postoperative Delirium in Patients Aged 75 Years or More After Major Abdominal Surgery

Abstract: PD is a frequent and severe postoperative event in elderly patients after major abdominal surgery. A perioperative geriatric assessment should be recommended to patients with an American Society of Anesthesiologists status of 3-4 and preoperative impaired mobility to facilitate the management of PD. In these patients, the postoperative administration of tramadol should be avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
158
4
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(171 citation statements)
references
References 38 publications
3
158
4
6
Order By: Relevance
“…In the study by Koebrugge et al, 29 the incidence of postoperative delirium after abdominal surgery was 24%. Brouquet et al 30 showed the same incidence of 24% of postoperative delirium in their study of elderly patients more than 75 years undergoing elective major abdominal surgery. In our study, poor preoperative mental state was not an exclusion criteria.…”
Section: Discussionmentioning
confidence: 68%
“…In the study by Koebrugge et al, 29 the incidence of postoperative delirium after abdominal surgery was 24%. Brouquet et al 30 showed the same incidence of 24% of postoperative delirium in their study of elderly patients more than 75 years undergoing elective major abdominal surgery. In our study, poor preoperative mental state was not an exclusion criteria.…”
Section: Discussionmentioning
confidence: 68%
“…In the older population, tramadol may cause fewer respiratory and gastrointestinal side-effects than other opioids, but is associated with delirium [58], and cannot be tolerated by a third of patients, due to nausea, vomiting, sweating, dizziness, tremors and headaches.…”
Section: Tramadolmentioning
confidence: 99%
“…In this study using ICDSC, considered very sensitive tool for screening of delirium, we found a POD incidence slightly inferior of that found by other authors. [18][19][20][21][22][23][24] . This lower incidence may be explained by the demographic characteristics of the study population with younger patients and a better preoperative status (patients with lower ASA-PS and lower RCRI).…”
Section: Discussionmentioning
confidence: 99%